The Comprehension of the Concept of Fath (Conquest) In the Light of Fath Al-Makkah - YÄ±lmaz, Dr. Mustafa Selim (JOURNAL OF SOCIAL SCIENCE RESEARCH, 2014)
Islam is the unique religion that calls itself peace. It also creates its concepts based on this name. Ironically, some various intellectual, religious and political groups are struggling to misinterpret Islam, which has such a deep-rooted peaceful background, and its concepts like jihad and fath (conquest) as it is the religion of war and point it out to be violent in every way in the global public opinion. In this article, it is tried to evaluate the concept of fath with the example of the Conquest of Makkah and interpret it faithful to its original. This example is peculiarly preferred because of that it is the beginning and the model of Islamic conquests. Furthermore, the main goal is frankly to protect human dignity in this example.